Protein Classification Using Neural Networks : A Review - Lee, Nung Kion; Wang, Dianhui; Tan, Kock Wah (Borneo Publisher Co, 2005)
This chapter presents an overview on the application of neural networks (NN) in bioinformatics, specifically in the classification of protein family/superfamily. Protein classification is important for both biological data analysis and knowledge discovery. NN has been one of the most widely used methods for protein classification. In this paper, detailed discussion of protein classification processes using NN is presented with emphasis on the various protein sequences feature extraction and neural classifier design. Some other related issues and future challenges are discussed at the end of the chapter.